Compensation for Damage Caused by a Crime in the Socialist Republic of Vietnam and the Russian Federation - Tien, Nguyen Van; Pushkarev, Viktor Victorovich; Tokareva, Ekaterina Viktorovna; Makeev, Alexey Vasilyevich; Shepeleva, Olga Rinatovna (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
In criminal proceedings of Vietnam, in contrast to the Code of Criminal Procedure of the Russian Federation, it is advisable to separate physical, material and moral damage that may be caused by the crime or socially dangerous act prohibited by the criminal law, the rights and legitimate interests of natural or legal persons. The article is devoted to solving the problem of compensation for damage caused by a crime in pre-trial proceedings in criminal cases, based on the study of Russian and Vietnamese criminal procedure legislation, practice, and results of its application. The conclusions are subject to study and implementation in the law.Keywords: Compensation for harm; Investigation; Rights and legitimate interests of participants in criminal proceedings Kompensasi untuk Kerusakan yang Disebabkan oleh Kejahatan di Republik Sosialis Vietnam dan Federasi Rusia Abstrak:Berbeda dengan Kode Acara Pidana Federasi Rusia, lebih baik dalam proses pidana Vietnam untuk memisahkan kerugian fisik, material, dan moral yang disebabkan oleh kejahatan atau tindakan berbahaya secara sosial yang dilarang oleh hukum pidana dari hak dan kepentingan sah orang atau badan hukum. Berdasarkan kajian undang-undang prosedur pidana Rusia dan Vietnam, praktik, dan hasil penerapannya, artikel ini dikhususkan untuk memecahkan masalah kompensasi atas kerusakan yang disebabkan oleh kejahatan dalam proses pra-persidangan dalam kasus pidana. Kesimpulan sedang dipelajari dan akan dimasukkan ke dalam undang-undang.Kata Kunci: Kompensasi untuk kerugian; Penyelidikan; Hak dan kepentingan sah peserta dalam proses pidana Возмещение вреда причиненного преступлением в социалистической республике Вьетнам и Российской Федерации АннотацияСтатья посвящена разрешению проблемы возмещения вреда, причиненного преступлением, в досудебном производстве по уголовным делам, на основе исследования российского и вьетнамского уголовно-процессуального законодательства, практики и результатов его применения. Выводы подлежат изучению и внедрению в законКлючевые Слова: возмещение вреда, расследование, права и законные интересы участников уголовного процесса, следователь, дознаватель